Perceived stress and its associated factors among pregnant women attending antenatal clinic in a tertiary level hospital - Pathak, Pratima; Ghimire, Bijaya (Journal of Karnali Academy of Health Sciences, 2024)
Background: Stress has been found widely prevalent among women during the time of pregnancy. Researches in different societies indicate a link between prenatal maternal stress and adverse obstetric, fetal, and neonatal outcome. Therefore, this study was carried out to assess perceived stress levels and associated factors with it among pregnant women.Methods: A descriptive cross-sectional study was carried out from November 2022 to March 2023 among 264 pregnant women attending the Obstetrics/Gynaecology outpatient department of Nepal Medical College and Teaching Hospital. Pregnancy Stress Rating Scale (PSRS) was adopted to measure perceived stress levels among pregnant women. Data were collected through face-to-face interview techniques. Descriptive statistics and logistic regression analysis were used for data analysis.Results: In this study, 11.4% (95% CI= 7.8% - 15.8%) of pregnant women had high levels of stress. Variables such as ethnicity, education of respondents and respondents’ husbands, status of pregnancy (pregnancy intention), and gender preference were associated with high levels of perceived stress in bivariate analysis. While, only those respondents having male gender preference for the upcoming baby was associated with a high level of stress (AOR= 3.07; 95% CI = 1.26 –7.48) in multivariate analysis.Conclusions: Approximately one out of nine pregnant women had a high level of stress in this study. Respondent’s gender preference for male babies was associated with high levels of stress in multivariate analysis. Therefore, early recognition of antenatal stress and its management is crucial.